PENGGUNAAN MODEL NARATIF EKSPERIENSIAL DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMA KATOLIK 2 KABANJAHE - Aldi Alfrianza Sinulingga; Maura Br Sitepu (Bahasa Indonesia Prima, 2023)
This research was conducted to find how using the Experiential Narrative model can increase the learning motivation of SMAK 2 Kabanjahe. This study uses a qualitative method. The qualitative method was chosen because it can explore a problem in – depth and can explain in detail explain in detail, from identifying a problem to explaining the solution. In This study used several techniques to collect the data, namely interviews, observation, and documentation. The research subject were 1 tutor, 1 school principal, and 10 social studies class X students. The study result show that: 1) Catholic Religious Education teachers' steps for using the experiential narrative model are reasonable. This can be seen from the teacher's ability to carry out the stages of the experiential narrative model before learning takes place. 2) The use of the experiential narrative model in learning has increased students' learning motivation. This can be seen from the positive response from students when the teacher teaches and the excellent good interaction between the teacher and students.